On the Contribution of Demographic Change to Aggregate Poverty Measures for the Developing World - Ravallion, Martin (World Bank, Washington, DC, 2012)
Recent literature and new data help determine plausible bounds to some key demographic differences between the poor and non-poor in the developing world. The author estimates that selective mortality-whereby poorer people tend to have higher death rates-accounts for 10-30 percent of the developing world's trend rate of "$1 a day" poverty reduction in the 1990s. However, in a neighborhood of plausible estimates, differential fertility-whereby poorer people tend also to have higher birth rates-has had a more than offsetting poverty-increasing effect. The net impact of differential natural population growth represents 10-50 percent of the trend rate of poverty reduction.